Analyzing future applications of AI, sensors, and robotics in society - Musiolik, Thomas Heinrich 1980-; Cheok, Adrian David (IGI Global, Publisher of Timely Knowledge, 2021)
"This book explores the future challenges and hidden potentials of the application of artificial intelligence, sensors, and robotics in society" - Provided by publisher
Keywords: Artificial intelligence; Detectors; Robotics